Centralized school management system using distributed database - Samayel, Sabid; Chowdhury, Ashikul Alam; Alam, Md. Shahidul (BRAC University, 2018)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.